Analysis of Growth Ratio, Effectiveness Ratio, and Efficiency Ratio in Bandung City - Rusdi, Renovita; Herawati, Olis; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Regional financial performance reflects the quality of financial management performance in a region. This research aims to analyse the financial performance of the Bandung City Government for the 2018-2022 budget year. The analysis was carried out by calculating the growth, effectiveness, and efficiency ratios based on the figures presented in the Bandung City APBD Budget Realization Report. This research uses quantitative descriptive analysis methods. The results of this research show that the financial performance of the Bandung City Government using the growth ratio is still not optimal because in 2020 there was a significant decline. The effectiveness ratio in 2018 and 2019 was categorised as less effective and experienced considerable development from 2020 to 2022 to the practical category. The efficiency ratio is classified as less efficient because the average value for 2018-2022 is 98.91%. The efficiency ratio in 2018-2020 continued to decline to below 100%, but in 2021-2022, it increased again until it reached above 100%, which means it became inefficient.